2012
DOI: 10.17221/5133-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dose of thymol and supplemental flavours or camphor on palatability in a choice feedings study with piglets

Abstract: Thymol’s antimicrobial properties urged researchers to study its effect on animal performance and intestinal health in pigs. However, thymol has the characteristic sharp odor of thyme and a bitter, aromatic, and sometimes burning sensation which may elicit feeding aversions. The objectives in the current study were: (1) to determine the effect of dose of thymol and camphor on palatability and (2) to test the hypothesis that supplemental flavours or camphor, the latter as a known Transient Receptor Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
0
13
1
Order By: Relevance
“…That the FA2 unfamiliar starter diet was preferred to the standard starter diet with no additive on the day of feed transition suggests that the FA2 has the ability to mask the change of feed and would be efficient to reduce the negative effect of feed neophobia and maintain feed intake during a sudden feed transition. Certain flavors and sensory additives have the ability to mask the negative properties of unpalatable ingredients, which results in increased feed intake and preferences for the flavoring diets in pigs (Baidoo et al, 1986;Tedò et al, 2008;Sulabo et al, 2010;Michiels et al, 2012). Roura et al (2007) also demonstrated the ability of certain aroma to mask the change of feed during a sudden feed transition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…That the FA2 unfamiliar starter diet was preferred to the standard starter diet with no additive on the day of feed transition suggests that the FA2 has the ability to mask the change of feed and would be efficient to reduce the negative effect of feed neophobia and maintain feed intake during a sudden feed transition. Certain flavors and sensory additives have the ability to mask the negative properties of unpalatable ingredients, which results in increased feed intake and preferences for the flavoring diets in pigs (Baidoo et al, 1986;Tedò et al, 2008;Sulabo et al, 2010;Michiels et al, 2012). Roura et al (2007) also demonstrated the ability of certain aroma to mask the change of feed during a sudden feed transition.…”
Section: Discussionmentioning
confidence: 99%
“…Yet such positive effects were expected given that the FA1 contained an extract of Stevia rebaudiana, with a minimum of 90% steviol glycosides (i.e., stevioside), which are the glycosides responsible for the sweet taste of stevia. Sweet taste is very attractive for pigs (Baldwin, 1976;Glaser et al, 2000;Nofre et al, 2002) and some sensory additives based on sweeteners are effective to increase feed palatability (Wahlstrom et al, 1974;McLaughlin et al, 1983;Michiels et al, 2012). According to electrophysiological studies, however, pigs are less sensible to steviol glyco-sides than humans (Hellekant and Danilova, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, Boudry & Perrier (126) , using the ex vivo Ussing chamber technique, showed that thymol induces Cland HCO 3 secretion of epithelial intestinal cells via a nervous pathway. Thymol and carvacrol also seem to activate TRPA1, which plays a role in pain sensation (40) , and this could be the reason why, for example, these phenols sometimes affect feed intake when fed at high doses and are not encapsulated (141) .…”
Section: Terpenesmentioning
confidence: 99%